2015
DOI: 10.1093/carcin/bgv099
|View full text |Cite
|
Sign up to set email alerts
|

Association between indel polymorphism in the promoter region of lncRNA GAS5 and the risk of hepatocellular carcinoma

Abstract: The growth arrest special 5 (GAS5) is known to be involved in various cancers. However, its expression regulation remains unclear. Polymorphisms in the promoter region of GAS5 may affect its expression and be associated with cancer susceptibility. In this research, we first evaluated the association of a 5-base pair indel polymorphism (rs145204276) in the promoter region of GAS5 with hepatocelluar carcinoma (HCC) susceptibility in Chinese populations. Logistic regression analysis showed that the deletion allel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
126
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(130 citation statements)
references
References 32 publications
3
126
1
Order By: Relevance
“…Growing data have revealed that SNPs in some lncRNAs are associated with chemotherapy response and tumorigenesis [22]. For example, the rs145204276 located in the promoter region of GAS5 has been reported to be an endogenous competing RNA of miR-21 [23][24][25]. Also, PDCD4 is believed to play a critical function in the pathogenesis of atherosclerosis by modulating the apoptosis of vascular endothelial cells [26,27], while our in-silicon analysis also found that miR-21 virtually targeted PDCD4.…”
Section: Introductionmentioning
confidence: 49%
See 1 more Smart Citation
“…Growing data have revealed that SNPs in some lncRNAs are associated with chemotherapy response and tumorigenesis [22]. For example, the rs145204276 located in the promoter region of GAS5 has been reported to be an endogenous competing RNA of miR-21 [23][24][25]. Also, PDCD4 is believed to play a critical function in the pathogenesis of atherosclerosis by modulating the apoptosis of vascular endothelial cells [26,27], while our in-silicon analysis also found that miR-21 virtually targeted PDCD4.…”
Section: Introductionmentioning
confidence: 49%
“…Interestingly, an earlier study has suggested that non-coding RNAs Zfas1 and GAS5 acted as tumor inhibitors, while the down-regulation of lncRNA GAS5 was found in prostate cancer, non-small cell lung cancer, breast cancer and renal cell carcinoma [30][31][32][33].Furthermore, an association between the rs145204276 polymorphism in the promoter region of GAS5 and the risk of HCC has also been identified. Moreover, rs145204276 may be functionally involved in oncogenesis via modulating the methylation status of a CpG island situated in the GAS5 promoter region, thus influencing the activity and expression of GAS5 [25]. In this study, we conducted luciferase reporter assays using vectors carrying rs145204276 polymorphism INS and DEL alleles to determine the effect of rs145204276 on the transcriptional activity of GAS5.…”
Section: Rs145204276 Polymorphism In the Promoter Region Of Gas5 Regumentioning
confidence: 99%
“…The rs145204276 polymorphism of promoter region of GAS5 was related to susceptibility to HCC. The SNP alters a CpG island methylation status in the GAS5 promoter region, and then the transcriptional activity of GAS5 and finally the expression level of GAS5 [15].The promoter region of GAS5 the deletion allele of a 5-base pair indel polymorphism (rs145204276) greatly enhanced the expression of GAS5 in hepatocellular cell lines and increased the risk of hepatocellular carcinoma (HCC), and it indicated that the GAS5 played differential roles in carcinogenesis of different cancer types [15]. To examine if the rs145204276 polymorphism influences the expression of GAS5, we conducted luciferase assay and found that that the deletion allele significantly increased luciferase activity of GAS5.…”
Section: Discussionmentioning
confidence: 99%
“…The negative relationship between miR-21 and GAS5 has been detected in clinical breast cancer specimens [14]. One variant (rs145204276 polymorphism), located in the promoter region of GAS5, could alter the transcription ability of the promoter [15]. GAS5 functions as a sponge of miR-21, which inhibits SMAD7 expression, and SMAD7 competitively inhibits another family member of SMAD3 [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, lncRNAs affect cell proliferation, migration, apoptosis, invasion, tumorigenicity, cell cycle, and metastasis. [11][12][13] Furthermore, evidence is accumulating to suggest that the aberrant expressions of lncRNAs have a clinical impact on the diagnosis of hepatocellular carcinoma. In this regard lncRNAs are associated with clinicopathological features including metastasis, invasion, TNM stage, prognosis, tumor size, and differentiation of patients with hepatocellular carcinoma.…”
Section: Introductionmentioning
confidence: 99%